Escape (Verse Version, 2025)
“Escape” is a poem of visceral immediacy and emotional intensity. Xiao Yi conveys the tension of fleeing, the pull of home, and the bodily experience of cold and displacement. The English version mirrors the Chinese original’s rhythm, imagery, and emotional force, capturing the urgent, almost cinematic pacing. The poem’s vivid symbols—red peach blossoms, crimson hair, starry nights—are highly charged and tactile in both languages. This bilingual presentation demonstrates the poet’s ability to retain emotional resonance across languages, making the work accessible yet deeply affecting in either version.